The contribution of the spatial dimension to inequality: A counterfactual analysis for OECD countries - Luis Ayala; Javier Martín-Román; Juan Vicente (Luxembourg Income Study (LIS), 2020)
This paper provides recent evidence on the contribution of the spatial dimension to inequality and more specifically accounts for the impact of the changes in the territorial distribution of the population on the recent dynamics of income inequality. We use LIS harmonized microdata for a selected sample of OECD countries. We provide new evidence over a more varied group of countries and a more recent period than in previous studies. We perform different types of decompositions to isolate the contribution of the changes in the territorial distribution of the population. The results show a generalized increase in income inequality, with an interesting "reducing effect" on this trend due to inter-territorial population movements.
Keywords: D31; D63; P52; 330; income inequality; regional inequality; decomposition methods; counterfactual analysis